Figurines. Figuration and The Sense of Scale - Jaś Elsner (Les Carnets de l’ACoSt)
This volume concerns figurines as archaeologically-attested materials from literate cultures with surviving documents that have no direct links of contiguity, appropriation, or influence in relation to each other.